Approaching the Lower Limits of Transgene Variability. - Mlynarova, L. (1996)
The inclusion of chicken lysozyme matrix-associated regions (MARs) in T-DNA has been demonstrated to reduce the variation in [beta]-glucuronidase (GUS) gene expression among first-generation transformed plants. The residual variation observed between transgenic plant lines with MARs at the T-DNA borders was investigated. By definition, any phenotypic variance between or within genetically identical plants is caused by random or environmental variation. This variation therefore sets a lower limit to the variation in GUS activities. The variance of GUS activity in offspring plant populations of genetically identical individuals was used as an estimate of environmental variation. For transgenic plants with MARs at the T-DNA borders, the variation between independent transformants could not be distinguished from the environmental variation. The variation could be attributed mainly to the variation in the GUS activity measurement. Therefore, the MAR element approached the maximal possible reduction of transgene variability given current technology and sample sizes. The role of MARs in offspring plants was evaluated by comparing such populations of transgenic plants for the magnitude of and variation in GUS activity. Pairwise comparisons showed that the presence of MARs reduced variation in offspring generations in the same manner as demonstrated for primary transformants. The populations carrying a doubled cauliflower mosaic virus 35S promoter-GUS gene tended to be more variable than the Lhca3.St.1 promoter-GUS gene-carrying populations. This tendency indicated an intrinsic susceptibility of the doubled cauliflower mosaic virus 35S promoter to variation. Homozygous plants were approximately twice as active as the corresponding hemizygous plants and tended to be more variable than the hemizygous plants. We hypothesized that the magnitude of environmental variations is related to a higher susceptibility to transgene silencing.